1993
DOI: 10.1111/j.1365-2109.1993.tb00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding frequency and feeding time on growth of Penaeus vannamei (Boone)

Abstract: Abstract. An intensive growth trial conducted In pens in an earthen pond indicated that growth of Penaeus vannamei (Boone) increased with feeding frequency and suggested that day feedings produce greater growth than night feedings. The differences in growth due to feeding frequency were significant, instantaneous growth rates (IGR) increasing from 1·62% to 1·66% to 1·71%/day as the number of feedings increased from one to two to four per 24 h. Comparison of the IGR of shrimp fed at night (1·64%/day) to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
3
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 14 publications
4
47
3
5
Order By: Relevance
“…Generally, studies on feeding frequency and its effect on shrimp growth are conflicting. Sedgwick (1979), Robertson et al (1993) and Tacon et al (2002) showed a positive effect on shrimp growth when feed frequency was increased. The present result also shows that feeding frequency has a great effect on growth performance and feed utilization of Nile tilapia fry.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, studies on feeding frequency and its effect on shrimp growth are conflicting. Sedgwick (1979), Robertson et al (1993) and Tacon et al (2002) showed a positive effect on shrimp growth when feed frequency was increased. The present result also shows that feeding frequency has a great effect on growth performance and feed utilization of Nile tilapia fry.…”
Section: Discussionmentioning
confidence: 98%
“…Los resultados sobre crecimiento en Litopenaeus vannamei realizados por Robertson et al (1993) sugieren que la alimentación durante las horas de luz, sería mejor que la alimentación nocturna. A su vez, Pontes & Arruda (2005) demostraron que L. vannamei accede a las bandejas de alimento e inicia un consumo rápido mostrando un mayor contenido en el tracto digestivo durante las horas de luz, por lo tanto estos resultados indican que el alimento debe ser ofrecido en la fase de luz, y en mayor proporción 7 h después del amanecer (Pontes et al, 2006).…”
Section: Discussionunclassified
“…De uma maneira geral, as informações específicas sobre comportamento de peneídeos, encontradas na literatura, afirmam que a maioria das espécies possui sulco adrostral e apresentam padrão de atividade similar (ROBERTSON et al 1993). Tipicamente, são ativas durante a noite e se enterram durante o dia (HINDLEY 1975).…”
Section: Resumo O Padrão Diário De Atividade De Litopenaeus Vannameiunclassified